Proximal Monitoring in Landscape Environments - Ng, Shuqi (Curtin University, 2017)
This thesis validates the use of stereo-cameras as a cost and time efficient technology to monitor environmental indicators. Tree dendrometrics can be measured quite accurately from stereo-images of trees. From these measurements, aboveground biomass is predicted using allometric models where the deviations from ground truth harvest data is smaller compared to traditional methods of estimation The prediction of tree biomass is of significance as it provides an effective non-destructive method for carbon accounting. This work was done in collaboration with CSIRO.